Melatonin exchange in infertile women with repeated implantation failures - O.M. Nosenko; R.Y. Demydchyk (Репродуктивная эндокринология)
Background. Repeated implantation failure occurs in approximately 10–15% of women undergoing in vitro fertilization and embryo transfer (IVF-ET) cycles. One of the important factors is the changed morpho-functional state of the endometrium and chronodestruction in the woman’s body.